2020
DOI: 10.3389/fphys.2020.622086
|View full text |Cite
|
Sign up to set email alerts
|

Co-Immunoprecipitation Reveals Interactions Between Amelogenin and Ameloblastin via Their Self-Assembly Domains

Abstract: Macromolecular assembly of extracellular enamel matrix proteins (EMPs) is intimately associated with the nucleation, growth, and maturation of highly organized hydroxyapatite crystals giving rise to healthy dental enamel. Although the colocalization of two of the most abundant EMPs amelogenin (Amel) and ameloblastin (Ambn) in molar enamel has been established, the evidence toward their interaction is scarce. We used co-immunoprecipitation (co-IP) to show evidence of direct molecular interactions between recomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 43 publications
3
34
0
Order By: Relevance
“…Protein–protein interactions involving IDPs are important for biomineralization. The ability of amelogenin and ameloblastin to self-assemble and interact with each other, with cell membrane, and with the mineral is associated with their IDP character and structural flexibility (Fan et al 2009; Delak et al 2009; Bapat et al 2020). Moreover, intrinsic disorder is a unique structural feature that enables these proteins to participate in many signaling events.…”
Section: Role Of Intrinsically Disordered Proteins In Enamel and Dentin Biomineralizationmentioning
confidence: 99%
See 4 more Smart Citations
“…Protein–protein interactions involving IDPs are important for biomineralization. The ability of amelogenin and ameloblastin to self-assemble and interact with each other, with cell membrane, and with the mineral is associated with their IDP character and structural flexibility (Fan et al 2009; Delak et al 2009; Bapat et al 2020). Moreover, intrinsic disorder is a unique structural feature that enables these proteins to participate in many signaling events.…”
Section: Role Of Intrinsically Disordered Proteins In Enamel and Dentin Biomineralizationmentioning
confidence: 99%
“…Amelx null mice develop enamel with a disorganized microstructure, but the fact that enamel still forms and ribbon-like calcium phosphate crystals are still present is an indication that other enamel proteins such as enamelin and ameloblastin are intimately involved in many aspects of mineral formation, including nucleation, phase transformation, and organized growth. Our recent in vitro and in vivo studies have demonstrated that amelogenin interacts directly with enamelin and with ameloblastin (Fan et al 2009; Gallon et al 2013; Bapat et al 2020). These studies support the notion of cooperative mechanisms between enamel matrix proteins in controlling processes of crystal nucleation and growth.…”
Section: Interactions Of Matrix Proteins In Enamelmentioning
confidence: 99%
See 3 more Smart Citations